Fabrication of Unidirectional Water Permeable PS/PET Composite Nanofibers Modified with Silver Nanoparticles via Electrospinning - Chong Li; Haoyu Wang; Xiaolei Zhao; Kaihua Yang; Qinhua Meng; Longwang Zhang (Membranes, 2023)
In this study, the composite nanofiber membranes (AgNPs-PS/PET) composed of hydrophobic polystyrene (PS) embedded with different additions of silver nanoparticles (AgNPs) and hydrophilic hydrolyzed polyethylene terephthalate (PET) were prepared via electrospinning technology to achieve the function of unidirectional water penetration. The addition of AgNO3 was at 0 wt%, 0.5 wt%, 1.0 wt% and 1.5 wt% as the variables. The surface morphology and structure of AgNPs-PS/PET composite nanofibers were characterized by scanning electron microscopy (SEM), x-ray energy dispersive spectroscopy (EDS) and transmission electron microscopy (TEM). The SEM image showed that the fibers of the composite materials were continuous and uniform as a result of electrospinning. The presence and content of Ag nanoparticles dispersed in the nanofibers were investigated using EDS and TEM. The contact angle (CA) was tested to illustrate the wettability of the composite nanofiber membranes using a static contact angle measuring instrument and the process of unidirectional water penetration was recorded. Meanwhile, the mechanism of unidirectional water penetration was analyzed. Moreover, the electrospinning solution’s viscosity and conductivity were also investigated. Eventually, the optimal addition of AgNO3 (1.0 wt%) was confirmed and the prepared AgNPs-PS/PET composite nanofiber membranes were able to achieve the function of unidirectional water penetration. These membranes have the potential to be applied in smart textiles, unidirectional water collection and wound dressing.